PENGARUH SELF EFFICACY DAN MOTIVASI TERHADAP KINERJA KARYAWAN (STUDI PADA PT. GEARINDO PRAKARSA SURABAYA) - ANDRIYANI, KIKI (Jurnal Ilmu Manajemen (JIM), 2017)
Human resources in the organization is a member who is expected to play a successful role organizational goals. Things to note by the company is the performance of employees, because the performance of employees greatly affect the development process of a company it self. Good performance is certainly supported by other factors such as self efficacy and motivation.PT. Gearindo Prakarsa Surabaya is a subsidiary of PT. Gearindo Prakarsa which engaged in the business of construction, electrical, mechanical. PT. Gearindo Prakarsa has implemented full commitmentpof ISO 9001: 2000o standard applied in all working procedures since 2003. The purpose of this research is to analyze the influence of self efficacy on employee performance and the influence of motivation on employeepperformance. Theusample usedpin thispstudy amountedpto 57 employeespof PT. Gearindo Prakarsa Surabaya. Analytical techniquekused is Structural Equation Model Partial Least Square with the help of SmartPLS software. They results of this study indicate that self efficacy has no significant peffect on employee performance and motivation has a significant effect on employeer performance. Keyword: Self Efficacy, Motivation, Employee Performance